Impaired immunosuppressive effect of bone marrow mesenchymal stem cell-derived exosomes on T cells in aplastic anemia - Shichong Wang; Jiali Huo; Yilin Liu; Lingyun Chen; Xiang Ren; Xingxin Li; Min Wang; Peng Jin; Jinbo Huang; Neng Nie; Jing Zhang; Yingqi Shao; et al. (Stem Cell Research & Therapy, 2023)
Abstract Background Previous studies have verified the dysfunction of mesenchymal stem cells (MSCs) for immunoregulation in acquired aplastic anemia (AA) patients. Exosomes derived from MSCs can partially substitute MSCs acting as immune regulator. Dysfunction of exosomes (Exos) derived from AA-MSC (AA-Exos) may play a key role in immunologic dissonance. Method In this study, CD3 + T cells were collected and cocultured with AA-Exos and exosomes derived from HD-MSC (HD-Exos). The proliferation, differentiation and activation of CD3 + T cells were detected to compare the immunosuppressive effects between AA-Exos and HD-Exos. An immune-mediated murine model of AA was structured to compare the therapeutic effect of AA-Exos and HD-Exos. Furthermore, total RNA including miRNA from exosomes we purified and total RNA of CD3 + T cells were extracted for RNA-seq in order to construct the miRNA–mRNA network for interactions and functional analysis. Results AA-Exos had impaired inhibition effects on CD3 + T cells in terms of cell proliferation, activation and differentiation compared with exosomes from HD-Exos. HD-Exos showed a more effective rescue of AA mice compared to AA-Exos. Importantly, we found some differentially expressed miRNA involved in immune response, such as miR-199, miR-128 and miR-486. The Gene Ontology analysis of differentially expressed genes (DEGs) revealed involvement of various cellular processes, such as lymphocyte chemotaxis, lymphocyte migration and response to interferon-gamma. The Kyoto Encyclopedia of Genes and Genomes analysis illustrated upregulation of critical pathways associated with T cell function after coculturing with AA-Exos compared with HD-Exos, such as graft-versus-host disease, Th17 cell differentiation and JAK-STAT signaling pathway. A miRNA–mRNA network was established to visualize the interaction between them. Conclusion In summary, AA-Exos had impaired immunosuppressive effect on T cells, less ability to rescue AA mice and differently expressed miRNA profile, which might partly account for the pathogenesis of AA as well as provide a new target of AA treatment.